The phenomenological confidence of the teacher in conducting learning projects - Rondinel Carrillo, Rosa Ines (2020)
The present research intends to capture in essence the meaning of teachers' experiences in relation to confidence in the management of learning projects, deepened through the hermeneutical phenomenological method, the qualitative approach and the interpretive paradigm. The sample was made up of teachers who were successful in the implementation of learning projects. They were asked to narrate an anecdote, used with a conversational interview as an instrument for collecting their experiences. From the analysis and interpretation of the data, individual thematic units emerged, such as individual physiognomy, motivation, values, confidence, mistrust, frustration, reflection, satisfaction, vocation, teamwork, autonomy and commitment. After categorization, the central theme or group physiognomy 'teacher confidence' reflected in the phenomenological text was conceived. It is concluded that, in environments of trust and security, comprehensive values are developed to optimize learning and project development.